Análise do líquido cefalorraquidiano nas manifestações neurológicas de pacientes adultos infectados pelo HIV - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
When compared to other causes of morbidity and mortality, such as cancer, opportunistic infections are the main causes of morbidity and mortality in people with HIV. People with HIV/AIDS who are not adequately treated with antiretroviral therapy develop neurological disorders associated with HIV. Between 40% and 70% of AIDS patients suffer from neurological complications, which have a significant impact on functional capacity and quality of life. The central nervous system is one of the main targets of HIV replication, and the second most common site where severe clinical manifestations are observed. The study's aim was to examine the cerebrospinal fluid of HIV patients with neurological manifestations at a reference hospital in infectious diseases in the city of Manaus, Amazonas. This is a descriptive, observational, retrospective study that investigated the cerebrospinal fluid of 18-year-old patients who evolved with neurological manifestations. Molecular diagnosis was used for the detection of viruses from the family Herpesviridae, JC virus, BK virus, Toxoplasma gondii, HTLV-1 and HTLV-2, and HIV. Ninety (36.7%) of the 245 cerebrospinal fluid samples from patients with neurological manifestations of PLWHA were found to contain pathogens, among them Cryptococcus sp. (7.7%), EBV (5.3%), CMV, VZV and JCV (4.0% each). HSV-1 and Mycobacterium tuberculosis were found in (0.8%) of samples, HSV-2 and BKV in (0.4%) samples. Seven patients (18.5%) had coinfection with two pathogens. T. gondii DNA was confirmed in 22 (30.5%) samples, being the most frequently detected pathogen. HIV RNA was detected in 68.8% (93/135) of the cerebrospinal fluid samples. The presence of opportunistic pathogens was detected in 36.7% of samples from people with neurological manifestations who are infected with HIV. T. gondii is the most common opportunistic agent among pathogens detected in these patients, and herpesviruses are important causes of changes in the CSF profile in these patients. There is a low positive correlation between the level of HIV RNA in CSF and plasma in our study group of patients. Despite the use of antiretroviral therapy, opportunistic central nervous system infections are still common in this population.
Keywords: Infecções oportunistas relacionadas com a AIDS; Infecções por HIV; Manifestações neurológicas; Líquido cefalorraquidiano; CIENCIAS DA SAUDE; HIV/AIDS; Manifestações neurológicas; Infecções oportunistas; Líquido cefalorraquidiano